Analysis of the self-healing capability of thermoplastic elastomer capsules in a polymeric beam structure based on strain energy release behaviour during crack growth - Almutairi, Mohammed Dukhi; He, Feiyang; Alshammari, Yousef Lafi A.; Alnahdi, Sultan Saleh; Khan, Muhammad Ali (MDPI, 2023)
The objective of this study was to investigate the elastic and plastic responses of 3D-printed thermoplastic elastomer (TPE) beams under various bending loads. The study also aimed to develop a self-healing mechanism using origami TPE capsules embedded within an ABS structure. These cross-shaped capsules have the ability to be either folded or elastically deformed. When a crack occurs in the ABS structure, the strain is released, causing the TPE capsule to unfold along the crack direction, thereby enhancing the crack resistance of the ABS structure. The enhanced ability to resist cracks was confirmed through a delamination test on a double cantilever specimen subjected to quasi-static load conditions. Consistent test outcomes highlighted how the self-healing process influenced the development of structural cracks. These results indicate that the suggested self-healing mechanism has the potential to be a unique addition to current methods, which mostly rely on external healing agents.
Keywords: 3D printing; TPE origami capsule; embedded structure; self-healing mechanism; double cantilever beam test